The New Bourgeoisie and the Limits of Dependency : Mining, Class, and Power in Revolutionary Peru - Becker, David G., 1938- (Book collections on Project MUSE., 1983)
The author clarifies the mutually constructive relationship between transnational and the modernizing Peruvian state, showing how the state maintains this relationship while simultaneously nurturing the new class. Originally published in 1983. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.